Strategies in Failure Management Scientific Insights, Case Studies and Tools (Management for Professionals,, 2018)
This book offers a comprehensive overview of failure in business, management and consulting. It features contributions by experts from diverse fields, who share unique insights from their real-life experiences. Readers will find perspectives from leadership, project management, change management, innovation management, human resource management, counseling, restructuring, entrepreneurship and sports. Each chapter combines the latest empirical findings with relevant case studies, making for a unique book that offers a fascinating exploration of the largely unexplored area of setbacks, pitfalls, flops and disappointments in the business world. .